2020
DOI: 10.3390/su12062405
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to the Promotion of Employee-Driven Innovation in State-Owned Enterprises: Two Cases from the Automotive Sector in China

Abstract: Employee-driven innovations (EDIs) are increasingly regarded as one of main source of innovation and sustainable competitive advantage, yet many studies indicate that EDIs are often undervalued in state-owned enterprises (SOEs) in China. It remains unclear what the challenges are to the promotion of EDIs in SOEs and how these challenges could be addressed with well-designed managerial practices such as a suggestion system. This study aims to address this research gap by studying two SOEs in the Chinese automot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Due to self‐interest, managers of SOEs have an inherent lack of innovation and entrepreneurship (Zhu et al, 2007). And it is difficult to promote employee‐driven innovation due to outsider control and short‐term tenure of top managers (Miao & Ji, 2020). Third is in terms of institutional theory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to self‐interest, managers of SOEs have an inherent lack of innovation and entrepreneurship (Zhu et al, 2007). And it is difficult to promote employee‐driven innovation due to outsider control and short‐term tenure of top managers (Miao & Ji, 2020). Third is in terms of institutional theory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Employers and employees enjoyed the open-ended reciprocal exchange, and SOEs attempted to create a moral bond with employees (Zhu et al, 2012). However, faced with increased competition, HRM practices in SOEs have moved towards so-called "transactional or differentiated" (p. 3964) practices to boost employees' performance (Zhu et al, 2012) and develop positive attitudes toward changes (Miao & Ji, 2020). These HRM practices include performance-based pay (Kehoe & Wright, 2013;Mac-Duffie, 1995), promotion, and increased competition among individuals (Miao et al, 2003).…”
Section: Human Resource Management Practicesmentioning
confidence: 99%
“…Being tightly controlled by the SASAC through stand-ard policies and formalized procedures, management teams in the SOEs and their divisions act more like state administrators than business executives (Miao & Ji, 2020). Their focus is obedience to SASAC rules and efficiency-based coordination to keep the organization functioning smoothly (Ralston et al, 2006).…”
Section: Central Control and Its Impacts On The Reciprocity Dynamics ...mentioning
confidence: 99%
“…In such a way, we argue that an organisation's capacity to be innovative and prompt a sustainability transition largely depends on its employees' creative ideas. As a matter of fact, studies across fields agree that the promotion of entrepreneurial behaviour -that is, the inclination to identify opportunities and introduce innovative ideas (Shane and Venkataraman, 2000) -within organisations is essential to foster innovation (see NBS, 2010;Weisnburger et al, 2018;Markopoulos, 2019;Miao and Ji, 2020;Hoyrup et al, eds.). On the contrary, if entrepreneurial behaviour is not appropriately harnessed, 'innovation remains little more than an aspirational destination than a sustainable, tangible one' (Coakes et al, 2011, p. 31).…”
Section: Green Identity Creativity and Intrapreneurshipmentioning
confidence: 99%
“…By analysing existing literature, the study has thus provided a multidisciplinary understanding of employeedriven innovation for organisational sustainability transition, which we referred to as 'employee-driven sustainability innovation' (EDSI) throughout the paper. The study concluded that EDSI could provide organisations with greater resilience against rapid and complex market changes by tapping into their employees' innovative potential and creating organisational cultures that promote continuous learning as well as innovative and intrapreneurial behaviours (for instance, see Høyrup, 2012;Miao and Ji, 2020;Buhl et al 2016 andHartmann, 1997). Secondly, it set out to understand what factors or processes can initiate EDI processes for organisational sustainability transitions.…”
Section: Key Findings On the Development Of Edsimentioning
confidence: 99%